Implementation model of data analytics as a tool for improving internal audit processes - Álvarez-Foronda, Rubén; De-Pablos-Heredero, Carmen; Rodríguez-Sánchez, José-Luis (Frontiers in Psychology, 2023)
Introduction The aim of this article is to understand the importance of internal audit departments todays—part of corporate governance and guardian of the organisation’s culture and climate—, as well as the opportunities that new technologies offer to increase their effectiveness and efficiency. Methods To this end, based on an exhaustive review of the literature, the concepts of internal audit and data analytics are related, and a framework is proposed for the implementation of a technology of these characteristics in an internal audit department. Results The results of the research show that those companies that invest resources in readapting their processes to technological change are likely to obtain better results than those organisations that keep their management procedures obsolete. Discussion Based on these results, it is concluded that there is a need to consider technological change in internal audit departments, specifically data analytics, to increase the effectiveness and efficiency of audit processes.